Nature-based Solutions as Building Blocks for coastal flood risk reduction: a model-based ecosystem service assessment - Massimiliano Marino; Martin J. Baptist; Ahmad I. K. Alkharoubi; Sofia Nasca; Luca Cavallaro; Enrico Foti; Rosaria Ester Musumeci (Scientific Reports)
Abstract Nature-based Solutions (NbS) are increasingly recognized as effective measures for mitigating flood risks and enhancing climate change adaptation. However, evaluating their efficacy in delivering flood risk reduction ecosystem service (FRR-ESS) is usually limited by reliance on qualitative, expert-based “quick-scan” scoring methods. While already challenging for present-day evaluations, this limitation becomes even more significant when addressing future climate scenarios, introducing deep uncertainties in the evaluation. The present study introduces a model-based framework to quantify FRR-ESS provided by coastal NbS, which integrates expert-based assessments with quantitative results from an eco-hydro-morphodynamic numerical model. The model enables a comparative evaluation of individual and combined effects of NbS following a Building Blocks approach. By integrating habitat map change prediction in the evaluation, NbS flood reduction response to present and future storm scenarios (i.e. wave climate and sea level rise) are investigated. The methodology is applied to a Mediterranean coastal lagoon in Sicily (Italy), and can be easily adapted to diverse coastal ecosystems. Our findings underscore the significant role of coastal habitats in reducing flood risk and highlight the importance of integrating physically-based modelling into FRR-ESS evaluation. This approach provides a robust and flexible tool for policymakers and stakeholders to make informed decisions that support both ecological sustainability and disaster risk reduction.